2018
DOI: 10.3389/fimmu.2018.00071
|View full text |Cite
|
Sign up to set email alerts
|

The Complement System in Dialysis: A Forgotten Story?

Abstract: Significant advances have lead to a greater understanding of the role of the complement system within nephrology. The success of the first clinically approved complement inhibitor has created renewed appreciation of complement-targeting therapeutics. Several clinical trials are currently underway to evaluate the therapeutic potential of complement inhibition in renal diseases and kidney transplantation. Although, complement has been known to be activated during dialysis for over four decades, this area of rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(121 citation statements)
references
References 107 publications
(164 reference statements)
5
116
0
Order By: Relevance
“…Many factors lead to inflammation in HD patients such as biocompatibility of the dialyzer membrane [ 73 , 74 , 75 ], infection related to dialysis access [ 73 ], and impure dialysate containing cytokine-inducing substances labeled as endotoxins [ 73 , 76 ].…”
Section: Iatrogenic Factors Of Malnutritionmentioning
confidence: 99%
“…Many factors lead to inflammation in HD patients such as biocompatibility of the dialyzer membrane [ 73 , 74 , 75 ], infection related to dialysis access [ 73 ], and impure dialysate containing cytokine-inducing substances labeled as endotoxins [ 73 , 76 ].…”
Section: Iatrogenic Factors Of Malnutritionmentioning
confidence: 99%
“…The cascade continues into production of C5a and C5b-9 during the next stages of dialysis. As reported by Poppelaars et al [26] during a single session of hemodialysis, the level designated to C5b-9 and C3d/C3 ratios in plasma (measures of complement system activation) reaches up to 70%. However this has been interpreted as an underestimation of the measures values as they are only calculated for fluid phase, while solid phase (deposited complement system's element on the surface) is not considered.…”
Section: Complement Activationmentioning
confidence: 55%
“…Protein attachment to the surface is commonly studied under the title of displacement processes (Vroman effect) which might initiate the coagulation cascade [24,25]. Any adhered cell (or triggered cells by the surface) could be activated, which consequently results in cascade activation (autocatalytic enzymatic processes) of other cells through production of mediators (with various purposes ranging from hindering interfacial cell adherence to defensive system activation) [26]. Defensive system activation in hemodialysis reflects hemoincompatibility of the used polymeric membrane.…”
Section: Membrane-blood Interaction and Biological Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Complement activation: the contact of plasma with the dialysis membrane can result in complement activation, which can lead to a pseudo-anaphylactic reaction called complement activation-related pseudoallergy (CARPA). 36 It has been shown that complement activation is related to the progression of cardiovascular disease (CVD). According to several studies, patients with higher C3 levels are more likely to develop CV events.…”
Section: Biocompatibilitymentioning
confidence: 99%